Al-Irsyad Al-Islamiyah: Keterbatasan Institusional dan Produksi Intelektual dalam Dakwah Pendidikan - Moh Mujib Karim; Affan Maulidi; Amir Maliki Abitolkha (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT This study aims to analyze the role of educational da'wah within the Al-Irsyad Al-Islamiyah movement and to identify institutional limitations that affect its intellectual production. Educational da'wah serves as a fundamental foundation for promoting the renewal of religious thought in Indonesia; however, in the contemporary context, it faces institutional constraints that hinder the optimal use of education as a basis for knowledge production. This research employs a qualitative approach with a library research design, analyzing relevant literature using historical-institutional, sociology of education, and capital theory approaches. The findings indicate that weak educational institutionalization directly affects the limited production of knowledge. The absence of representative higher education institutions, the limited accumulation of social, economic, and symbolic capital, and the lack of a structured academic cadre system have resulted in sporadic intellectual production that has not developed into a sustainable scholarly tradition. Therefore, strengthening Al-Irsyad requires institutional transformation through the development of higher education, the strengthening of academic cadre formation, and the establishment of an integrated and sustainable knowledge-production ecosystem. Keywords : Al-Irsyad Al-Islamiyah, institutional limitations, knowledge production.